Performance Optimization of Masonry Mortar with Marble Dust, Spent Coffee Grounds, and Peanut Shell Ash - Beskopylny, Alexey N.; Hematibahar, Mohammad; Momeni, Komeil; Stel'makh, Sergei A.; Shcherban', Evgenii M. (Salehan Institute of Higher Education, 2025)
This research focused on the inclusion of spent coffee grounds (SCGs) and peanut shell ash (PSH) as variable additives and marble dust as a constant additive to cement materials to substitute aggregates and determine the effect of each variable on the properties of cement materials. To determine the influence of PSH and SCGs, these were added to mortar in 0.1, 0.2, and 0.3% proportions and were combined with microsilica and superplasticizer. To analyze the results, the compressive and flexural strengths during three-point bending were investigated. The chemical composition and microstructure of the mortar mix were investigated using Scanning Electron Microscopy (SEM) and Energy-Dispersive X-ray (EDX) spectroscopy. The results showed that incorporating microsilica into the mortar mix increased the compressive strength to over 35.42 MPa compared to the control sample's 33.4 MPa. Adding 0.1% and 0.3% of SCGs and PSH improved the compressive strength of the mortar mix to over 39.48 and 38.09 MPa, respectively. Including 0.2% SCGs and 0.1% PSH increased the flexural strength to over 4.52 and 6.0 MPa, respectively. The SEM and EDX results showed that adding 0.3% SCGs slowed down the formation of calcium silicate hydrates (C-S-H), consequently slowing down the hydration processes, and the strength gain was slower compared to microsilica. The addition of 0.3 PSH stimulated the formation of C-S-H, additionally supplying the cement matrix with such elements as Si and Al. Overall, adding SCGs and PSH has a positive effect on the mechanical and chemical properties of the mortar mix, although adding PSH is more beneficial than adding SCGs. Doi: 10.28991/CEJ-2025-011-03-09 Full Text: PDF